NSTTF Heliocon Wireless Closed-Loop Controls Test Bed Development - Kenneth Armijo; Haden Harper; Zachary Bernius; Claus Danielson; Ansel Blumenthal; Luis Garcia-Maldonado (SolarPACES Conference Proceedings)
A closed loop controls test bed is in development at the Sandia National Laboratories (SNL), National Solar Thermal Test Facility (NSTTF) as part of the U.S. DOE SETO sponsored Heliostat Consortium (HelioCON) program. This work pertains to preliminary development of advanced feedback controls for a concentrating solar power (CSP) field of 218 heliostats, and the development of a baseline closed-loop controls extremum seeking control (ESC) algorithm. This algorithm utilizes a batch least squares (BLS) technique to facilitate feedback control automation for heliostat pointing. This allows the determination of the optimal highest flux within a Gaussian profile, for both a four-point (QuadCell) aim point strategy, and a concentric aim point strategy. The results of this work determined that both approaches using the ESC BLS were able to reduce pointing errors to zero for both azimuth and elevation heliostat position movements. This work also reviews progress of the test bed which will allow flexible employment of controls and sensors which will be communicating with both wired and wireless protocols. The solar field distributed control system (DCS) will manage the flux distribution of energy across test articles and solar receivers using real-time programmable logic controllers (PLC) at each heliostat, for aiming and closed-loop feedback. Feedback control will be facilitated with a variety of sensors, located: 1. On the heliostat, 2. On the tower or 3. At an ancillary field tower station. The system is also developed to incorporate environmental information to provide real-time feedback into advanced algorithms for solar field management.